Church lawyer and defense law - Leszczyński, Grzegorz (Prawo Kanoniczne, 2024)
In the context of the right to defense, the institution of the church lawyer appears. This concerns in particular the question: does the participation of a church lawyer in the process for determining the invalidity of a marriage guarantee the right to defense of the party to the proceedings, does this right secure and does the presence of a church lawyer have any significance in guaranteeing the right to defense? Does it have any reference to the right to defense of the party to the proceedings at all, or is the presence of a lawyer only an aid in maintaining the formal side of the process or the substantive aspect of the party's interest in the proceedings? In my opinion, the honest performance of one's opinion serves to guarantee the right to defense of the party to the proceedings. This does not mean that the presence of a lawyer is necessary, but it can certainly help to guarantee the right to defense. This applies to the individual stages of the process, which were mentioned above.